A decision support tool for rubble stabilization on coral reefs - Shu Kiu Leung; Tania M. Kenyon; Laurie J. Raymundo; Helen E. Fox; Nathan Cook; Kailash Cook; Alasdair J. Edwards; Eric E. Fisher; Arnaud J.T. Brival; Freda E. Nicholson; Robin W.L. Philippo; Andrew C.F. Taylor; et al. (Journal of Environmental Management, 2025)

Dynamic changes in physicochemical properties, flavor, and microbial communities during kombucha fermentation with dominant autochthonous strains inoculation - E. Liao; Na Liu; Qian Li; Han Li; Lu Wang; Wenmin Wu (Food Research International, 2025)

Emission characteristics of full-volatility organic compounds from China's aluminum-products industry and their impacts on secondary organic aerosol and ozone potentials - Dongyang Wu; Qing'e Sha; Shan Jiang; Luyun Liu; Citao Zhang; Jialin Song; Junhao Xu; Haoqi Chen; Guanghui Li; Zhangmin Xiang; Bin Jiang; Zhuangmin Zhong; et al. (Environmental Research, 2025)

C/N-Driven Synergies: Earthworms optimize CO2/N2O mitigation and soil quality in floral waste recycling - Hongyang Li; Guijun Wu; Mei Li; Changqun Duan; Chang-e Liu (Environmental Research, 2025)

Simulation of carbon fluxes from Tibetan Plateau grasslands by integrating data assimilation and parameter inversion within the Biome-BGC model - Jingzhou Zhang; Tao Zhou; Li Cao; Jingyu Zeng; Yajie Zhang; Qi Zhang; Xuemei Wu; Yancheng Qu; E. Tan; Xia Liu (Ecological Modelling, 2025)

Modulating charge separation in g-C3N4 via synergistic carbon self-doping and nitrogen defects engineering for enhanced photocatalytic H2 evolution and CO2 reduction - Samuel Guemou; Fazal E. Haq; Cheng Cheng; Huaiwu Peng; Kang Chen; Yu Chen; Xin Li; Maochang Liu; Jinwen Shi (Chemical Engineering Journal, 2025)

The fate of multiple antibiotics in a counter-diffusion biofilm system carrying out short-cut nitrification and denitrification when treating saline wastewater - Ting Li; Mingxuan Lyu; Boyang Hu; Yi Li; Yuan Zhang; Hao Liu; Baoan Li; Bruce E. Rittmann (Chemical Engineering Journal, 2025)

Palaeoecological reconstruction of shoreline terrestrialisation of Lake Glubokoe (Smolensk-Moscow Upland) in the late Holocene based on the results of a multi-proxy analysis - Yulia A. Pastukhova; Andrey N. Tsyganov; Natalia G. Mazei; Elena E. Severova; Dmitrii O. Sadokov; Viktor A. Chernyshov; Ekaterina V. Tkacheva; Jinyue Li; Yanwei Liu; Alexey A. Kotov; Andrey V. Kitashov; Ping Ding; et al. (Journal of Paleolimnology, 2025)

Prof Stephen P. Long, FRS (1950–2025) - Lorenzo Álvarez‐Filip; Edith Bai; Carl J. Bernacchi; Rhea Bruno; Klaus Butterbach‐Bahl; Maria Byrne; I‐Ching Chen; Shaolin Chen; William W. L. Cheung; M. Francesca Cotrufo; Tatenda Dalu; Xiaojuan Feng; et al. (Global Change Biology, 2025)

High Quality, Granular, Timely, Trustworthy and Efficient Vertebrate Species Distribution Data Across a 30,000 km 2 Protected Area Complex - Yinqiu Ji; Alex Diana; Xueyou Li; Eleni Matechou; Jim E. Griffin; Shuwei Liu; Mingjie Luo; Chunying Wu; Ru Bai; Chenyang Yao; Tingting Yin; Feng Dong; et al. (Ecology Letters, 2025)
The routine generation of species distribution data at scale remains a challenge. We used aquatic environmental DNA metabarcoding to sample vertebrate species across the 30,000 km 2 Gaoligongshan region along the China–Myanmar border. In just 56 calendar days (33 researcher‐field‐days + 69 researcher‐lab‐days), we detected 389 vertebrate species, of which 35 are Red‐Listed. We introduce the ‘eDNA‐aware’ OccPlus occupancy model, which accounts for false‐negative and false‐positive error in the field and lab. OccPlus leverages the taxonomic breadth of eDNA datasets by using ordination to estimate species occupancies. We recover known biogeographic patterns and find that native terrestrial and fish species have higher occupancies inside protected areas while domesticated species and non‐native fishes have higher occupancies outside them. Our study demonstrates how eDNA metabarcoding can obtain high‐quality, granular, timely, trustworthy and efficient species distribution data to facilitate nature conservation and restoration.

The role of protein post-translational modifications and their crosstalk in determining pluripotent stem cells fate - Wenhui Fan; Taoxia E; Bin Lu; Hongyan Sun; Keshi Chen; Xingguo Liu; Linpeng Li (Science Bulletin, 2025)

Metabolomics combined with 16S rDNA revealed the effects of low protein diet on rumen microbiome structure, nitrogen utilization rate and differential metabolites in feces and urine of dairy cows - Yaqiong Ren; Caijuan Yue; Wenzhuo Wang; Li Cai; Yanming Wang; Xiaojing Liu; Depeng Li; Qiao'’e Zhang (Research in Veterinary Science, 2025)

Dual-strategy stabilization of zinc anodes through solvation regulation and interfacial engineering in aqueous zinc ion batteries - Weilin Yan; Yifan Wang; Lufan Liu; Feiyu Tao; Yang Huang; Zhaoqian Li; Li'e Mo; Hong Zhang; Linhua Hu (Chemical Engineering Journal, 2025)

Differential effects of Ca2+ and Mn2+ on cyanobacterial mineralization and organic matter preservation - Jie Li; Yongjie Zhang; Yanyang Zhao; Chao Han; Kaiming Hu; Wenhui Chen; Yangmei Fei; Yongmei Liu; Haoran Li; Maurice E. Tucker; Zuozhen Han (Chemical Geology, 2025)

Bio-organic fertilizer amendment helps suppress tomato bacterial wilt disease by improving aggregation and enhancing the pathogen inhibition capacity within micro-aggregates - Menghui Dong; Eiko E. Kuramae; Mengli Zhao; Yi Min; Shanshan Liu; Xu Xu; Qirong Shen; Rong Li; George A. Kowalchuk (Biology and Fertility of Soils, 2025)

Mycorrhizal allies: synergizing forest carbon and multifunctional restoration - Tengteng Li; Richard P. Phillips; Matthias C. Rillig; Gerrit Angst; E. Toby Kiers; Paola Bonfante; Nico Eisenhauer; Zhanfeng Liu (Trends in Ecology & Evolution, 2025)

NH3, N2O, NO and NO2 losses, emission factors and reduction mechanisms under different N managements from greenhouse vegetable soils - Tiantian Miao; Bin Wang; Yunfan Wan; Yu'e Li; Tianjing Ren; Huan Liu; Jiaqi Zhang; Andong Cai; Waseem Hassan (Journal of Environmental Management, 2025)

Cadmium stress drives remodeling of earthworm mucus metabolism: Hormetic antioxidant response and synergistic amino acid defence mechanisms - Guijun Wu; Changqun Duan; Hongyang Li; Mei Li; Chang-e Liu (Environmental Research, 2025)

Efficient Hg(II) removal using recyclable poly(thioctic acid)/SH-UiO-66 functionalized polyacrylonitrile fiber: Multifunctional binding strategy - Ningge Jian; Gaoran Zhang; Hongli Liu; Di Wu; Jia Wang; Yuxin Wang; Yi Cheng; Qingyuan Liu; Yongjun Wu; Li-e Liu (Chemical Engineering Journal, 2025)

Multi-electron donation promotes the photocatalytic conversion of carbon dioxide to methane in a covalent bonded metal-complex/quantum dots hybrid catalyst - Qian Zhao; Mohamed Abdellah; Yang Liu; Jie Meng; Xianshao Zou; Kasper Enemark-Rasmussen; Yu Zhou; Yi Li; Yuehan Cao; Yijiang Chen; Nora Eliasson; Ying Zhou; et al. (Chemical Engineering Journal, 2025)

Reestablished buried interface by multifunctional additive for high-efficiency perovskite solar cells - Xiaoli Zhang; Fobao Xie; Bing’e Li; Xinghan Zeng; Chuangping Liu; Qinghua Cao; Jiangping Xing; Eugene Troyan; Baihong Zheng; Hui Liu; Andrey Stepanov (Chemical Engineering Journal, 2025)

Recognition of novel metal-resistant microbes and their potential resistance mechanisms in metal mines - Ting Li; Chang'e Liu; Chenyang Zhang; Changqun Duan (Applied Soil Ecology, 2025)

Surface-based morphometry reveals divergent aging trajectories in veterans with and without traumatic brain injury - Michelle C. Eliason; Amrutha Bindu Nagella; Cristian Cuadra; David S. Wack; Ghazala T. Saleem; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowki; Arthur W. Toga; et al. (GeroScience, 2025)

Magnetite-augmented sulfur-siderite autotrophic denitrification: Deep nitrogen removal at ultra-low HRT from lab to pilot scale - Jiale Sun; Haoyong Li; He Dong; Lu Liu; Chunyv Zhou; Ziwen Du; Yan Dang; Dawn E. Holmes (Water Research, 2025)

Nitrogen fixation in Pampinifervens, a new species-rich genus of Aquificaceae that inhabits a wide pH range in terrestrial hot springs - Marike Palmer; Nancy O. Nou; Lara A. Turello; Carolyn E. Power; John C. Ong; Jonathan K. Covington; Dengxun Lai; Xavier Mayali; Anna-Louise Reysenbach; Yan-Ling Qi; Jeremy A. Dodsworth; Jian-Yu Jiao; et al. (Systematic and Applied Microbiology, 2025)

Petrogenesis of the olivine cumulate outcrop Issole – The missing link between the Séítah and Máaz formations in Jezero crater, Mars - Juan David Hernández-Montenegro; Tanya V. Kizovski; Allan H. Treiman; An Y. Li; Paul D. Asimow; Mariek E. Schmidt; Yang Liu; Josh Labrie; Abigail L. Knight; Michael M. Tice; David A. Klevang; Scott VanBommel; et al. (Icarus, 2025)

Simultaneous N-methyl pyrrolidone and total-nitrogen removals in a single aerobic process - Fei Liu; Meng Huang; Chenyu Li; Linlin Chen; Yongming Zhang; Bruce E. Rittmann (International Biodeterioration & Biodegradation, 2025)

Millet stable isotopes reveal the advance of agricultural practices in the core political regions of early imperial China - Jingwen Liao; Edward Allen; Amanda G. Henry; Jason E. Laffoon; Ming Li; Daiyun Liu; Pengfei Sheng (CATENA, 2025)

Remobilization of Ni in framboidal pyrite within sulfide nodules in Early Cambrian nickeliferous black shales - Xu-Yang Liu; Ya-Fei Wu; Daniel D. Gregory; Katy Evans; Anthony E. Williams-Jones; Wen Zhang; Mei-Fu Zhou; Jian-Wei Li (Chemical Geology, 2025)

JsSAMDC promotes polyamine synthesis and flowering genes to synergistically regulate female flower bud differentiation - Jinyan Chen; Wenwen Li; Chunxiang Li; Yuanqi Huang; Jian Peng; Dong Huang; Mengmeng Liu; Xuejun Pan; Wen’ e Zhang (Plant Cell Reports, 2025)

Air quality and mental health amid COVID-19: a prospective population-based analysis of the mediating role of daily routine disruptions - Selina Kit Yi Chan; Crystal Jingru Li; Percy Poo-see Tse; Evon Lam Wong; Anan Wang; Huinan Liu; Stevan E. Hobfoll; Chi Yung Jim; Wai Kai Hou (Air Quality, Atmosphere & Health, 2025)

Enhanced sulfamethoxazole (SMX) degradation by Shewanella oneidensis MR-1 via a microbially driven Fenton reaction - Qing-Jiahui Fan; Wei Li; Gen-Ji Yao; Zu-Hao Wang; Han Fu; Yong-Di Liu; Bruce E. Rittmann (Journal of Water Process Engineering, 2025)

Enhancing ecological risk assessment of dioxins in aquatic environments: AHR diversity and species sensitivity differences in tiger puffer (Takifugu rubripes) - Zhenhong Xue; Wanglong Zhang; Anran Ren; Sibel I. Karchner; Diana G. Franks; Yanjiao Zong; Yongchao Ma; Jiayi Wang; Yiqin Xu; Jiaming Li; Ning Ding; Chunchen Liu; et al. (Journal of Hazardous Materials, 2025)

Quality changes in the physiology, behaviour, nutrition, and taste of Urechis unicinctus during waterless live transportation - Teng Teng; Yuchun Lu; Zichen Deng; Shuqi Wang; Yuting Yang; Huihong Li; Chun-E Liu (Food Chemistry, 2025)

Early life phthalate exposure impacts gray matter and white matter volume in infants and young children - Emily J. Werder; Kun Lu; Chih-Wei Liu; Jake E. Thistle; Julia E. Rager; Gang Li; Zhengwang Wu; Tengfei Li; Li Wang; Dale P. Sandler; John H. Gilmore; Joseph Piven; et al. (Environmental Research, 2025)

Sociodemographic, medical, health behavior, and psychosocial factors associated with COVID-19 diagnoses in the New Jersey cancer survivor cohort - Sharon Manne; Adana A. M. Llanos; Hari S. Iyer; Lisa E. Paddock; Katie Devine; Shawna V. Hudson; Denalee O’Malley; Elisa V. Bandera; Sara Frederick; Jacintha Peram; Justin Solleder; Shengguo Li; et al. (Cancer Causes & Control, 2025)
Background Cancer survivors are more susceptible to contracting COVID-19. However, beyond race, age, and sex, less is known about other neighborhood and psychosocial factors contribute to this increased risk. Objective The goal of this study was to examine the associations of individual and area-level social determinants of health (SDOH) measures, medical, lifestyle, and psychosocial factors and COVID-19 infection in a statewide cohort of cancer survivors in New Jersey. Methods Survey data from 864 cancer survivors in New Jersey were collected from 2018 to 2022, which were merged with study participant data from the state of New Jersey on COVID-19 diagnoses in 2020, 2021, and 2022. We estimated adjusted odds ratios (aOR) for associations of COVID-19 diagnosis with individual-level factors (cancer type and stage, health behaviors, and psychosocial factors) and area-level SDOH [Social Vulnerability Index, Area Deprivation Index, and Index of Concentration at the Extremes (ICE) to quantify racialized deprivation vs. privilege based on income]. Results Cancer survivors born outside the US were more than twice as likely to contract COVID-19 compared to US-born survivors (aOR 2.29, 95% CI 1.01, 4.92). Compared to Quartile 4, residence in an area in Quartile 1 of racialized income ICE (i.e., predominantly Black, low income) was associated with higher odds of COVID-19 (aOR 2.15, 95% CI 0.98, 4.87). Retired survivors had lower odds of COVID-19 (aOR 0.39, 95% CI 0.19, 0.80) compared to those who were employed. Higher social well-being was associated with higher COVID-19 (aOR 1.07, 95% CI 1.02, 1.13). Type of cancer and cancer treatments received were not associated with the risk of COVID-19. Conclusions Immigrant status and increased racialized deprivation as measured by ICE for income were associated with COVID-19. These findings support evidence that individual and area-level SDOH measures contribute to increased risk of COVID-19 among cancer survivors.

On the long and winding road: unravelling the late emergence of Neolithic agriculture in the Nile Delta - Xiaoshuang Zhao; David Kaniewski; Yanna Wang; Nick Marriner; Alaa Salem; Said E. Alassal; Yan Liu; Feng Jiang; Jing Chen; Qianli Sun; Maotian Li; Ian Thomas; et al. (Quaternary Science Reviews, 2025)

Clinical biomarkers of perioperative neurocognitive disorder: initiation and recommendation - Jianhui Liu; Cheng Li; Junyan Yao; Lei Zhang; Xuan Zhao; Xin Lv; Zhiqiang Liu; Changhong Miao; Yingwei Wang; Hong Jiang; Weifeng Yu; Tianlong Wang; et al. (Science China Life Sciences, 2025)

Characteristics and evolution of mass-transport complex since Late Miocene in the Zengmu and Beikang basins, southern South China Sea - Shuqin Huang; Ming Su; Haiteng Zhuo; Li Zhang; Shan Liu; Zhi Lin Ng; Zhixuan Lin; Boda Zhang; Kunwen Luo; Li’e Lin (Journal of Oceanology and Limnology, 2025)

Behavioral Responses of Migratory Fish to Environmental Cues: Evidence from the Heishui River - Jiawei Xu; Yilin Jiao; Shan-e-hyder Soomro; Xiaozhang Hu; Dongqing Li; Jianping Wang; Bingjun Liu; Chenyu Lin; Senfan Ke; Yujiao Wu; Xiaotao Shi (Fishes, 2025)
Hydropower infrastructure has profoundly altered riverine connectivity, posing challenges to the migratory behavior of aquatic species. This study examined the post-passage migration efficiency of Schizothorax wangchiachii in a regulated river system, focusing on upstream and downstream reaches of the Songxin Hydropower Station on the Heishui River, a tributary of the Jinsha River. We used radio-frequency identification (RFID) tagging to track individuals after fishway passage and coupled this with environmental monitoring data. A Cox proportional hazards model was applied to identify key abiotic drivers of migration success and to develop a predictive framework. The upstream success rate was notably low (15.6%), with a mean passage time of 438 h, while downstream success reached 81.1%, with an average of 142 h. Fish exhibited distinct diel migration patterns; upstream movements were largely nocturnal, whereas downstream migration mainly occurred during daylight. Water temperature (HR = 0.535, p = 0.028), discharge (HR = 0.801, p = 0.050), water level (HR = 0.922, p = 0.040), and diel timing (HR = 0.445, p = 0.088) emerged as significant factors shaping the upstream movement. Our findings highlight that fishways alone may not ensure functional connectivity restoration. Instead, coordinated habitat interventions in upstream tributaries, alongside improved passage infrastructure, are crucial. A combined telemetry and modeling approach offers valuable insights for river management in fragmented systems.

Biotic and abiotic drivers of soil carbon, nitrogen and phosphorus and metal dynamic changes during spontaneous restoration of Pb–Zn mining wastelands - Sichen Wang; Ting Li; Xinqi Yuan; Ji Yu; Zhifei Luan; Zhaolai Guo; Yadong Yu; Chang’e Liu; Changqun Duan (Journal of Hazardous Materials, 2025)

Record High Temperatures in the Ocean in 2024 - Lijing Cheng; John Abraham; Kevin E. Trenberth; James Reagan; Huai-Min Zhang; Andrea Storto; Karina Von Schuckmann; Yuying Pan; Yujing Zhu; Michael E. Mann; Jiang Zhu; Fan Wang; et al. (Advances in Atmospheric Sciences, 2025)
Heating in the ocean has continued in 2024 in response to increased greenhouse gas concentrations in the atmosphere, despite the transition from an El Niño to neutral conditions. In 2024, both global sea surface temperature (SST) and upper 2000 m ocean heat content (OHC) reached unprecedented highs in the historical record. The 0–2000 m OHC in 2024 exceeded that of 2023 by 16 ± 8 ZJ (1 Zetta Joules = 10 21 Joules, with a 95% confidence interval) (IAP/CAS data), which is confirmed by two other data products: 18 ± 7 ZJ (CIGAR-RT reanalysis data) and 40 ± 31 ZJ (Copernicus Marine data, updated to November 2024). The Indian Ocean, tropical Atlantic, Mediterranean Sea, North Atlantic, North Pacific, and Southern Ocean also experienced record-high OHC values in 2024. The global SST continued its record-high values from 2023 into the first half of 2024, and declined slightly in the second half of 2024, resulting in an annual mean of 0.61°C ± 0.02°C (IAP/CAS data) above the 1981–2010 baseline, slightly higher than the 2023 annual-mean value (by 0.07°C ± 0.02°C for IAP/CAS, 0.05°C ± 0.02°C for NOAA/NCEI, and 0.06°C ± 0.11°C for Copernicus Marine). The record-high values of 2024 SST and OHC continue to indicate unabated trends of global heating.

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

The molecular mechanism of electrical stimulation on enhancing the foaming properties of egg white liquid - E. Zhao; Chan Li; Jing Yuan; Keshan Wang; Jingchun Ma; Ying Zhou; Qiujin Zhu; Xiaoli Liu; Yongguo Jin; Yuanyuan Liu (Food Hydrocolloids, 2025)

Dual-interface induced bandgap regulated water-based flexible interactive generator - Ye Zhou; Pengcheng Wu; Yuchang Zhu; Huoerhute Yelemulati; Shanshan Zhu; Keliang Wu; Guihua Meng; Hao Wang; Fathy Hassan; Mohsen Sherif; Guanglin Li; Zhiyong Liu; et al. (Chemical Engineering Journal, 2025)

Linking soil extracellular enzymes with soil respiration under altered litter inputs - Hao Chen; Qianhao Xu; Kees Jan van Groenigen; Bruce A. Hungate; Pete Smith; Dejun Li; Daryl L. Moorhead; Brooke B. Osborne; Zilong Ma; Jørgen E. Olesen; Chaoqun Wang; Ji Liu; et al. (Agricultural and Forest Meteorology, 2025)

Global Patterns of Climatic Niche Evolution in Angiosperms - Yunpeng Liu; John J. Wiens; Ao Luo; Xiaoting Xu; Dimitar Dimitrov; Xiangyan Su; Yichao Li; Tong Lyu; Loic Pellissier; Niklaus E. Zimmermann; Douglas E. Soltis; Pamela S. Soltis; et al. (Global Ecology and Biogeography, 2025)
Aim A species' rate of climatic niche evolution may reflect its ability to survive changing climates. Yet large‐scale studies of these rates remain limited. Here, we assessed global patterns in climatic niche rates among angiosperms and explored the potential drivers shaping these patterns. Location Global. Time Period Current. Major Taxa Studied Angiosperms. Methods We estimated broad‐scale climatic niches for 231,567 angiosperm species based on distributional data from over 1100 sources. By integrating a published phylogeny of angiosperms, we estimated rates of climatic niche change for each extant species as the difference between its current and ancestral niche divided by the species' age. Global patterns were analysed by averaging rates for all the species found in each geographic unit. We used multiple statistical models to explore the relative contributions of niche width and climatic seasonality to shaping these geographic patterns of niche evolution. We analysed patterns of niche evolution and their underlying drivers separately for temperature‐related and precipitation‐related niches and for different directions of niche evolution (i.e., increases and decreases in species' temperature and precipitation niche values when compared to their most recent ancestors). Results Rates for temperature variables increased with latitude, whereas rates for precipitation variables decreased with latitude. These opposing patterns in temperature and precipitation rates were related to opposing latitudinal patterns in climatic seasonality and species' niche widths for temperature and precipitation. Rates also differed for different directions of niche evolution, with different patterns associated with changes to warmer vs. cooler climates and wetter vs. drier climates. Main Conclusions Our results revealed large‐scale geographic patterns in rates of climatic niche change for temperature and precipitation for the largest clade of angiosperms and their underlying drivers. These findings may have important implications for species' abilities to respond to recent climate change.

Exosomes secreted from M2-polarized macrophages inhibit osteoclast differentiation via CYLD - Zi-yan Guo; Nan-nan Yin; Xiao-fei Li; Meng-meng Wang; Xiao-na Sui; Cai-di Jiang; Ming-hua Xu; Xiao-e Jia; Chong-jian Fu; Tie-lou Chen; Xin Liu (Tissue and Cell, 2025)

An ingenious integrated metal-organic frameworks-based ratiometric sensing platform for efficient, sensitive and real-time detection of tetracyclines - Yueyi Shen; Li-e Liu; Tong Li; Ruili Liu; Jingyi Zhang; Jiaojiao Chen; Xuqing Zhang; Xinyi Li; Ningge Jian; Di Wu (Food Chemistry, 2025)

Enhancing the adsorption capacity of lignin-based super activated carbon for trace toluene under highly humid conditions through [2 + 1] cycloaddition reactions - Zhenrui Li; Haifeng Zuo; Minglei Su; Zhenbing Sun; Jianfeng Ma; Xing’e Liu; Pengyi Zhang (Chemical Engineering Journal, 2025)

Genetic advancements and future directions in ruminant livestock breeding: from reference genomes to multiomics innovations - Songsong Xu; Zhanerke Akhatayeva; Jiaxin Liu; Xueyan Feng; Yi Yu; Bouabid Badaoui; Ali Esmailizadeh; Juha Kantanen; Marcel Amills; Johannes A. Lenstra; Anna M. Johansson; David W. Coltman; et al. (Science China Life Sciences, 2025)

Voxel-wise insights into early Alzheimer’s disease pathology progression: the association with APOE and memory decline - Maha Wybitul; Nicolas Langer; Christoph Hock; Anton Gietl; Valerie Treyer; Michael Weiner; Paul Aisen; Ronald-Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; et al. (GeroScience, 2025)
Longitudinal investigation of the Apolipoprotein E (APOE) genotype’s impact on Alzheimer’s disease (AD) biomarker progression, focusing on amyloid beta (Aβ) accumulation and gray matter (GM) atrophy, integrating cognitive decline and baseline levels. Longitudinal florbetapir-PET and T1-weighted MRI data from 100 cognitively normal (CN) and mild cognitive impaired (MCI) participants both with considerable global Aβ accumulation (“high Aβ accumulators”) were analyzed using a voxel-wise approach. Associations of APOE genotype and memory decline with Aβ accumulation and GM atrophy were examined separately for each neuroimaging modality, controlling for baseline Aβ levels and diagnosis. Alternatively, the effect of baseline diagnosis, while controlling for memory decline, was investigated. A multimodal analysis evaluated interactions between genotype, memory decline, and GM atrophy on Aβ accumulation. High Aβ accumulators displayed extensive Aβ pathology predominantly in the medial orbito-frontal cortex, cingulate cortex, and precuneus, along with GM atrophy in temporal, occipital, orbito-frontal, and parietal areas. ɛ4 carriers with memory decline exhibited greater Aβ accumulation and GM atrophy in selective regions compared to non-carriers with memory decline, while no genotype difference was observed in individuals without decline. No interaction effect was observed for MCI diagnosis. Regional associations between the two biomarkers were similarly dependent on genotype and memory decline. ɛ4 carriers exhibiting memory decline present an accelerated neurobiological pattern at predementia stages, supporting early ɛ4 carrier monitoring and interventions in this at-risk group. Importantly, memory decline might be more informative than MCI regarding AD pathology progression emphasizing the importance of repeated cognitive assessments.

Screening of Spinal Muscular Atrophy Carriers and Prenatal Diagnosis in Pregnant Women in Yancheng, China - Huilin Sun; Jianli Zheng; Qing’e Zhang; Feifei Ying; Yadong Fu; Yongjuan Guan; Jing Wu; Yueyun Zhou; Jingjing Dong; Mengjun Xu; Fangfang Yang; Ning An; et al. (Biochemical Genetics, 2025)

Mo4+-Pb2+ redox triggers self-enhanced removal and recovery of Pb2+ with superselectivity - Yang Yu; Yangqi E; Hetao Liu; Qian Li; Huachang Jin; Xueming Chen; Jianmeng Chen; Dongzhi Chen (Water Research, 2025)

The association between anthropogenic heat and parent-report symptoms of childhood attention deficit hyperactivity disorder in China: A novel perspective reflecting climate change - Tao Yu; Yue Wen; Pei-Pei Dong; Ming-Kun Sun; Samantha E. Qian; Mario Schootman; Michael G. Vaughn; Shu-Li Xu; He-Hai Huang; Feng-Wen Shan; Shi-Fu Zhu; Jing-Yao Wang; et al. (International Journal of Hygiene and Environmental Health, 2025)

GRANDlib: A simulation pipeline for the Giant Radio Array for Neutrino Detection (GRAND) - R. Alves Batista; A. Benoit-Lévy; T. Bister; M. Bohacova; M. Bustamante; W. Carvalho; Y. Chen; L. Cheng; S. Chiche; J.M. Colley; P. Correa; N. Cucu Laurenciu; et al. (Computer Physics Communications, 2025)

The effect of heatwave and cold spell on cardiovascular disease mortality in central China, 2018–2022 - Ling-Shuang Lv; Li Yin; Yuan Liu; Chun-Liang Zhou; Ji Hu; Ning An; Xian Xie; Xing-E Zhang; Min Zhang; Xiu-Ying Liu (International Journal of Biometeorology, 2025)

Temperature drives reproductive activity in a rare trioecy population of Corbicula clams - Jie Pi; Yangxin Tang; Neil E. Coughlan; Linwei Liu; Xu Wang; Xinhua Liu; Jianguo Xiang; Deliang Li (Hydrobiologia, 2025)

Critical assessment of missense variant effect predictors on disease-relevant variant data - Ruchir Rastogi; Ryan Chung; Sindy Li; Chang Li; Kyoungyeul Lee; Junwoo Woo; Dong-Wook Kim; Changwon Keum; Giulia Babbi; Pier Luigi Martelli; Castrense Savojardo; Rita Casadio; et al. (Human Genetics, 2025)
Regular, systematic, and independent assessments of computational tools that are used to predict the pathogenicity of missense variants are necessary to evaluate their clinical and research utility and guide future improvements. The Critical Assessment of Genome Interpretation (CAGI) conducts the ongoing Annotate-All-Missense (Missense Marathon) challenge, in which missense variant effect predictors (also called variant impact predictors) are evaluated on missense variants added to disease-relevant databases following the prediction submission deadline. Here we assess predictors submitted to the CAGI 6 Annotate-All-Missense challenge, predictors commonly used in clinical genetics, and recently developed deep learning methods. We examine performance across a range of settings relevant for clinical and research applications, focusing on different subsets of the evaluation data as well as high-specificity and high-sensitivity regimes. Our evaluations reveal notable advances in current methods relative to older, well-cited tools in the field. While meta-predictors tend to outperform their constituent individual predictors, several newer individual predictors perform comparably to commonly used meta-predictors. Predictor performance varies between high-specificity and high-sensitivity regimes, highlighting that different methods may be optimal for different use cases. We also characterize two potential sources of bias. Predictors that incorporate allele frequency as a predictive feature tend to have reduced performance when distinguishing pathogenic variants from very rare benign variants, and predictors trained on pathogenicity labels from curated variant databases often inherit gene-level label imbalances. Our findings help illuminate the clinical and research utility of modern missense variant effect predictors and identify potential areas for future development.

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

Research landmarks on the 60th anniversary of Epstein-Barr virus - Lan-Yi Zhong; Chu Xie; Le-Le Zhang; Yan-Lin Yang; Yuan-Tao Liu; Ge-Xin Zhao; Guo-Long Bu; Xian-Shu Tian; Zi-Ying Jiang; Bo-Yu Yuan; Peng-Lin Li; Pei-Huang Wu; et al. (Science China Life Sciences, 2025)

Contribution of China’s carbon budget on global radiative forcing - Nan Li; Yaoping Cui; Xiaoyan Liu; Zhifang Shi; Mengdi Li; Michael E. Meadows (Journal of Geographical Sciences, 2025)

Bifunctional probe propelling multipath strand displacement amplification tandem CRISPR/Cas12a for ultrasensitive and robust assay of DNA methyltransferase activity - Fei Yu; Qiongwen Zhang; Tiantian Ma; Shuying Zhang; Fanting Wang; Dan Yue; Shihan Liu; Yueqi Liao; Li-e Liu; Yongjun Wu; Wenqiao Zang (Analytica Chimica Acta, 2025)

A study on the runoff prediction mechanism of “water-soil-heat” in cold alpine regions with complex spatial distribution - Qiying Yu; Yungang Bai; Zhenlin Lu; Chengshuai Liu; Shan-e-hyder Soomro; Wenzhong Li; Lu Tian; Yingying Xu; Chen Shi; Biao Cao; Caihong Hu (Science of The Total Environment, 2025)

How Rhodococcus ruber accelerated biodegradation of benzophenone-3 - Fei Liu; Yue Ma; Wenxuan Li; Jue Cai; Haiyun Zhang; Fu Chen; Yongming Zhang; Bruce E. Rittmann (Journal of Hazardous Materials, 2025)

Effects of rumen metabolite butyric acid on bovine skeletal muscle satellite cells proliferation, apoptosis and transcriptional states during myogenic differentiation - Xiao-Wei Wang; Yan-Ling Ding; Cheng-Long Li; Qing Ma; Yuan-Gang Shi; George E Liu; Cong-Jun Li; Xiao-Long Kang (Domestic Animal Endocrinology, 2025)

Novel synthesis of sulfur-doped Ag3PO4 photocatalyst for efficient degradation of cylindrospermopsin - Xu Zhang; Li Zhou; Yiyang Liu; E Hengchao; Zhiyong Zhao; Huaqiang Chu; Xuefei Zhou; Yalei Zhang; Guoyan Zou (Chemical Engineering Journal, 2025)

pH-Responsive lignin-modified copper-based metal-organic frameworks for precision thiamethoxam delivery in the targeted control of red imported fire ants (Solenopsis invicta) - Pengpeng Liu; Amir E. Kaziem; Chen Li; Xin Wang; Shiqi Zhu; Jinzhe Chang; Dongmei Cheng; HanHong Xu; Zhixiang Zhang; Liupeng Yang (Chemical Engineering Journal, 2025)

Influence of land-use type on earthworm diversity and distribution in Yunnan: Insights from soil properties - Chang-E Liu; Qing-Rui Luo; Yan-Lan Xiao; Hong-Yang Li; Hong-Juan Dong; Chang-Qun Duan (Applied Soil Ecology, 2025)